Nanocellulose Bio-Based Composites for the Removal of Methylene Blue from Water: An Experimental and Theoretical Exploration - Sanchez-Poblete, J; Roa-Ruiz, K; Oyarce-Riveros, E; Boulett-Neira, A; Boulett-Neira, A (Elsevier B.V., 2022)
In this work, we synthesized new bio-composites as adsorbents to remove methylene blue (MB) from aqueous solutions. These hydrogels, based on 2-hydroxyethylmethacrylate (HEMA), were prepared by free-radical copolymerization with itaconic acid (IA) or acrylic acid (AA) monomers in combination with different amounts of cellulose nanofiber (CNF). The mass yield percent in all the synthesized materials is over 94%. The bio-composites were characterized by Fourier transform infrared spectroscopy (FT-IR), thermal gravimetric analysis (TGA), and scanning electron microscopy (SEM) techniques. The capacity to absorb water and to remove MB was determined through batch studies. FT-IR and TGA analysis reveals the molecular structure of the polymers and its good stability in the temperature range of 25–490 °C. In addition, highly porous morphology was observed by SEM. Bio-composites prepared with a higher percentage in mass of CNF showed a MB removal efficiency of approximately 100% for poly (2-hydroxyethylmethacrylate-co-itaconic acid) with 2% CNF (P(HEMA-co-IA)-2%CNF) and 80% for poly (2-hydroxyethylmethacrylate-co-acrylic acid) with 2% CNF (P(HEMA-co-AA)-2%CNF), where the maximum adsorption capacity was 467.51 mg g−1 for P(HEMA-co-IA)-2%CNF and 339.90 mg g−1 for P(HEMA-co-AA)-2%CNF. Furthermore, after three adsorption-desorption cycles in an acidic medium (pH 1.0), both hydrogel systems decreased their adsorption efficiency by approximately 20%. From a theoretical point of view, the most stable conformation showed that CNF and MB molecules prefer to move to different areas of the polymer network, avoiding a direct interaction. However, in the polymeric network there are energetically favourable contacts between MB, and CNF. The intermolecular interactions are predominantly dominated by weak interactions such as London dispersion and electrostatic interactions between charged groups. Molecular dynamics (MD) simulations help to identify the existence of π-π stacking interactions between aromatic rings from MB in the polymeric network. Contact interactions were characterized by the non-covalent interaction index (NCI) index. © 2022 Elsevier B.V.